Hyperlactatemia and Lactic Acidosis Results in Longer Stay in Intensive Care Units (ICUs) and Development of Co-morbid in Post-operative Cardiac Surgery Patients - Alam, Junaid Mahmood; Ahmed, Aijaz; Sultana, Ishrat; Mahmood, Syed Riaz (International Journal of Innovative Research in Medical Science, 2016)
Pathology of Hyperlactatemia and lactic acidosis is convoluted, including tissue hypoxia, pulmonary abnormalities, Ischemic shock, hypohemoglobinemia and generalized an-aerobic conditions. All or any one of these conditions may have occurred due to surgical intervention, long-term cardiogeneic syndromes or after long Intensive care stay. Present study described the assessment and correlation of post-operative Hyperlactatemia in cardiac surgery patients to the longer length of stay in Intensive care units (ICUs). Pre-operative and Post operative blood samples were analyzed in seventy five (Males = 59, females = 16) cardiac surgery patients for Lactate and other biochemical parameters were according to the prescribed methods. Post-operative blood sample analyses were also performed 4-6 hrs after surgery and after 24 hrs post-operatively. Six hours postoperative assessment of lactate, showed alerted levels, manifesting post-operative complications and development of co-morbid. It was also noted that patients (n = 21) with higher lactate >20mg/dl had to stay longer in ICUs (12-18 days stay, average 16.15 ± 2.50 days) as compared to those (n = 54) with normal range of lactate level (5-9 days stay, average 7.20 ± 2.10 days). It is thus concluded that post-operative Hyperlactatemia and lactic acidosis in cardiac surgery patients is a significant condition to detect poor outcome. Additionally post-operative lactate level can predict length of stay in ICUs and any prospect of developing adverse outcome and co-morbid.